2017
DOI: 10.1111/acem.13301
|View full text |Cite
|
Sign up to set email alerts
|

“What Do People Do If They Don't Have Insurance?”: ED‐to‐ED Referrals

Abstract: The majority of patients presenting to a public hospital ED after treatment for the same complaint in another local ED were indirectly referred to the public ED without transferring paperwork or records, incurring duplicate testing and patient anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Prior studies have shown that privately insured patients, even with severe injuries, are less likely to be transferred out of non-trauma center hospitals than uninsured or Medicaid patients. 76,77,78,79,80,81 Consequently, unintended consequences associated with either adjusting or not adjusting for sociodemographics need to be carefully considered. 82…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that privately insured patients, even with severe injuries, are less likely to be transferred out of non-trauma center hospitals than uninsured or Medicaid patients. 76,77,78,79,80,81 Consequently, unintended consequences associated with either adjusting or not adjusting for sociodemographics need to be carefully considered. 82…”
Section: Discussionmentioning
confidence: 99%